2018
DOI: 10.25026/mpc.v8i1.295
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lama Penyimpanan Terhadap Aktivitas Antioksidan Ekstrak Daun Miana (Coleus atropurpureus L. Benth)

Abstract: Daun miana (Coleus atropurpureus L. Benth.) merupakan tumbuhan yang memiliki aktivitas antioksidan alami.Tujuan penelitian ini yaitu untuk mengetahui pengaruh lama penyimpanan terhadap aktivitas antioksidan dan flavonoid totalekstrak daun Miana (Coleus atropurpureus L. Benth.) pada penyimpanan suhu sejuk. Dilakukan pengujian flavonoid total serta uji aktivitas antioksidanmenggunakan metode DPPH (1,1-difenil-2-pikrilhidrazil) dan diukur dengan spektrofotometer UV-Vis, kemudian dihitung nilai IC50. Hasil penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…It was found that fresh apples have a lower quercetin content than (Ventiyaningsih et al, 2016). Room temperature storage can also reduce antioxidant activity such as quercetin as evidenced in previous studies that at room temperature storage, rosella flower extract decreased antioxidant activity (Khotimah et al, 2018).…”
Section: Examination Of Quercetin Levelsmentioning
confidence: 80%
“…It was found that fresh apples have a lower quercetin content than (Ventiyaningsih et al, 2016). Room temperature storage can also reduce antioxidant activity such as quercetin as evidenced in previous studies that at room temperature storage, rosella flower extract decreased antioxidant activity (Khotimah et al, 2018).…”
Section: Examination Of Quercetin Levelsmentioning
confidence: 80%
“…Therefore, based on the test results, it can be concluded that the addition of 200 mL and 300 mL of noni juice with a fermentation time of 7 days had a significant effect on increasing the antioxidant activity of kombucha. The DPPH test measures antioxidant activity by involving the oxidation and reduction process of antioxidant compounds, such as phenols produced in the fermentation process by SCOBY microorganisms, with DPPH compounds [9]. A fermentation time of 7 days is more optimal for increasing antioxidant activity because drinks fermented for more than 10 days are at risk of damage due to organic acid fertilization.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Lama penyimpanan juga berpengaruh terhadap total flavonoid, karena semakin singkat lama penyimpanan, proses oksidasi senyawa flavonoid akan semakin singkat pula. Hal ini dibuktikan pada penelitian Khotimah et al (2018) melaporkan bahwa pada penyimpanan ekstrak daun miana hari pertama pada suhu 8-15℃ setelah penyimpanan hari ke-3, 7 dan 14 kadar flavonoid total mulai mengalami penurunan yaitu pada hari ke-3, ke-7 dan ke-14 berturut-turut sebesar 10,62%, 10,18% dan 10,01%…”
Section: Total Flavonoidunclassified